Osteointegration of poly(L-lactic acid)PLLA and poly(L-lactic acid)PLLA/poly(ethylene oxide)PEO implants in rat tibiae - Coraca, Debora Cristina; Duek, Eliana Aparaecida R.; Padovani, Carlos A. [UNESP]; Camilli, Jose Angelo (Springer, 2008)
Natural or synthetic materials may be used to aid tissue repair of fracture or pathologies where there has been a loss of bone mass. Polymeric materials have been widely studied, aiming at their use in orthopaedics and aesthetic plastic surgery. Polymeric biodegradable blends formed from two or more kinds of polymers could present faster degradation rate than homopolymers. The purpose of this work was to compare the biological response of two biomaterials: poly(L-lactic acid)PLLA and poly(L-lactic acid)PLLA/poly(ethylene oxide)PEO blend. Forty four-week-old rats were divided into two groups of 20 animals, of which one group received PLLA and the other PLLA/PEO implants. In each of the animals, one of the biomaterials was implanted in the proximal epiphysis of the right tibia. Each group was divided into subgroups of 5 animals, and sacrificed 2, 4, 8 and 16 weeks after surgery, respectively. Samples were then processed for analysis by light microscopy. Newly formed bone was found around both PLLA and PLLA/PEO implants. PLLA/PEO blends had a porous morphology after immersion in a buffer solution and in vivo implantation. The proportion 50/50 PLLA/PEO blend was adequate to promote this porous morphology, which resulted in gradual bone tissue growth into the implant.